An exploratory comparative study of experts and generalists as change management leaders in non-core areas of organizations - BURTON, Steven Glenn (Institutional Knowledge at Singapore Management University, 2018)
Large-scale organizational change is a necessary undertaking critical to the ongoing success of most firms. Despite the necessity of such change, it is also an undertaking that fails at approximately twice the rate that it succeeds. Prior work on change leadership primarily looks at characteristics of the individual leader and does not differentiate on areas of the organization where change will be occurring. The work conducted in this research compares categories of change leaders and looks at change within a specific area of a firm, its non-core business area. This exploratory research compared core-area technical experts to generalists as change leaders in non-core areas of their firm. It sought to identify if differences existed between these two groups in leading non-core-area change in these four areas: 1) recognition of need for change, 2) motivation to lead change 3) perception of skills to lead change and 4) perception of empowerment to lead change. A multi-step grounded theory approach was used to develop the research questions, propositions and hypotheses. This was followed by a two-stage survey of expert and generalist leaders in higher education institutions. The results showed that while experts were perceived to be empowered and to possess some of the necessary skills, they demonstrated little intrinsic motivation to contribute in non-core-area change leadership. Instead, they preferred to contribute in their expert technical area. Generalists also were perceived to possess some of the necessary skills to lead change, and they demonstrated a higher level of recognition of the need for change and a significant preference to contribute in the area of non-core-area change leadership. However, they were perceived as not possessing sufficient empowerment to be a non-core-area change leader. This foundational exploratory work is presented to both provide practice-based guidance for firms, as well as establish a base for future work to further the field of study. Looking at categories of change leaders (experts and generalists in this work) in specific areas of an organization (non-core in this work) appears to be a lightly researched area. However, with the consequences of not changing or of suffering failed changes being potentially fatal to an organization, guidance that can come from further research in the area is a topic of great importance and worthy of continued research.